Aortic and Mitral Valve Replacement Due to Extensive Inflammatory Immunoglobulin G4–Related Pseudotumor - Besik, Josef; Pirk, Jan; Netuka, Ivan; Szarszoi, Ondrej; Marek, Tomas; Urban, Marian; Honsova, Eva; Laco, Jan (The Annals of thoracic surgery, 2015)
A 64-year-old woman with extensive tumorous infiltration of the mitral and aortic valves underwent partial resection of a tumor of the left ventricular outflow tract and replacement of both affected valves. Histology revealed an inflammatory pseudotumor with a significant number of immunoglobulin-G4–positive plasma cells. The histologic and clinical findings suggested immunoglobulin-G4–related disease of the heart.